Reliability of heart rate responses both during and following a 6 min Yo-Yo IR1 test in highly trained youth soccer players. Issue 1 (2nd January 2019) - Doncaster, Greg; Scott, Mark; Iga, John; Unnithan, Viswanath
ABSTRACT: Purpose : To examine the reliability of heart rate (HR) measures obtained during a 6-min Yo-Yo Intermittent Recovery Test Level 1 (Yo-Yo IR1), and following a 3-min passive recovery, within a group of highly trained youth soccer players Methods : Eight players completed three separate 6-min Yo-Yo IR1 tests, with a passive recovery, over a 2-week period. Measures of absolute heart rate (bpm) and relative HR (%HRmax ) were obtained at the 3 rd and 6 th min of the test, with measures relative to the end HR (%HRend ) 10, 20, 30, 60, 90, and 180 s, during the 3-min passive recovery. Variability in HR measures were assessed across successive trials (trial 1 vs. 2 and trial 2 vs. 3) and across all three trials, using the intraclass correlation coefficient (ICC), coefficient of variation (CV) and typical error (TE). Results : HR measures obtained during the 6-min Yo-Yo IR1 test displayed good levels of reliability (ICC: 0.95–0.98, CV: 1.1–1.3% and TE: 0.96–2.44). Results, display a potential learning effect, with lower levels of variability between trial 2 and trial 3. Examination of %HRend obtained during the passive 3-min recovery demonstrated an increased variance, as the passive-recovery period progressed. Conclusion : The 6-min Yo-Yo IR1 test presents a novel and potentially practical approach to regularly assessing youth soccer players' physical response to intermittent exercise. Practitioners and researchers should, however, consider the need for appropriate familiarisation when undertaking this test.